Financial Services Innovation: Local Strategy, Management, and Change – A Field Investigation - Ann-Catherine Nave (Pursuit - The Journal of Undergraduate Research at the University of Tennessee, 2012)
This study examines the innovation sources and processes of regional financial services firms through inductive field research. Innovation in these firms, and presumably other financial services firms and other smaller organizations, originate primarily out of three sources, the drive for efficiency, the external environment, and strategic, ambidextrous management. Successfully innovative firms balance the short-term need for efficiency improvements with the long-term desire to grow primarily through visionary, yet adaptive, leadership.
Keywords: Finance; Banking